(untitled) (Research, Society and Development, 2022)
Syzygium cumini (L.) Skeels is an important species of the Myrtaceae family, because of its different fates in folk medicine. Due to its high biological activity, jambolan has been studied a lot lately. Thus, the objective of this work was to evaluate the antimicrobial action and analyze the cytotoxicity of the extract and fractions of S. cumini. First, phytochemical tests were carried out to recognize the secondary metabolites present in the extract, with subsequent disk diffusion test to investigate the ability of inhibiting bacterial growth of the extract against gram-negative bacteria Klebsiella pneumoniae Escherichia coli and gram-positive, Streptococcus mutans . The microemulsion was produced from physical-chemical tests and cytotoxicity was performed in fibroblast-like cells. The phytochemical prospection of the hydroethanolic extract obtained the presence of secondary metabolites, such as: Flabobens, Flavones, Flavonols, Xanthones, Flavononois, Leucoanthrocyanidins, Catechins, Steroids and Saponins. The active fraction of the extract, in this case Ethyl Acetate, inhibited bacterial growth, being incorporated into the microemulsion, which also showed antimicrobial activity, enabling the formulation of the product.